Pelatihan Terpadu Agribisnis Hortikultura Dalam Rangka Optimalisasi Lahan Di Desa Setiris, Kecamatan Maro Sebo, Kabupaten Muaro Jambi: Penelitian - Elwamendri; Yanuar Fitri; Yusma Damayanti; Dewi Sri Nurchaini; Yulismi; Zakky Fathoni; Riri Oktari Ulma; Liona Efrina; Edison (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community engagement program aimed to empower women's farmer groups through horticultural cultivation training, focusing on water spinach (kangkung), to optimize the use of yard land owned by the PKK Danau Keman group in Setiris Village, Maro Sebo Subdistrict, Muaro Jambi Regency. The PKK Danau Keman group consists of 20 members who had not previously utilized their 10 m² yard effectively. Using a participatory extension method, the members were equipped with practical knowledge and skills in horticultural cultivation, including land preparation, planting, harvesting, and product marketing. The results show that all members were able to implement cultivation techniques independently. The harvested kangkung is regularly sold, contributing to the group’s income. This activity not only improved technical skills but also enhanced women's roles in food security and household economy. The program proved effective as a community-based empowerment model that can be replicated in similar regions